A New Critically Endangered Species of Nissolia (Leguminosae, Papilionoideae, Dalbergieae) from Brazil and a New Combination in the Genus - Fortuna Perez, Ana Paula [UNESP]; Lewis, Gwilym Peter; Castro, Isabella [UNESP]; Veiga, Vitoria Floss da [UNESP]; Machado, Silvia Rodrigues [UNESP]; Moura, Tania Maria de (Amer Soc Plant Taxonomists, 2021)
Nissolia rondonensis, a new critically endangered species from the state of Rondonia, Brazil, is described and illustrated. Its distribution, informal conservation status, phenology, and morphological and anatomical affinities with its closest relative, Nissolia klugii, are discussed. In addition, a new combination, Nissolia subulata is proposed. A key to the Brazilian species of Nissolia is presented.
Keywords: Chaetocalyx; Fabaceae; South America; taxonomy